2020
DOI: 10.1101/2020.06.01.20118943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Greater risk of severe COVID-19 in non-White ethnicities is not explained by cardiometabolic, socioeconomic, or behavioural factors, or by 25(OH)-vitamin D status: study of 1,326 cases from the UK Biobank

Abstract: Background We examined whether the greater severity of coronavirus disease 2019 (COVID-19) amongst men and non-White ethnicities is explained by cardiometabolic, socio-economic, or behavioural factors. Methods We studied 4,510 UK Biobank participants tested for COVID-19 (positive, n=1,326). Multivariate logistic regression models including age, sex, and ethnicity were used to test whether addition of: 1)cardiometabolic factors (diabetes, hypertension, high cholesterol, prior myocardial infarction, smoking, BM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…However, the Norwegians in the cited study had far higher vitamin D levels than the UK Biobank participants at their initial evaluation, a subset increased their 25(OH)D levels significantly (p < 0.001) by initiating supplements, and, as in the study by Meng et al, vitamin D levels did increase significantly for the group as a whole over time (p < 0.01) (81). The authors of the most recent article using the UK BioBank study data did not address the issue of the use of potentially no longer accurate 25(OH)D levels in their preprint, but added a reference to the same Norwegian study as Darling et al, in their published article (77).…”
Section: Irish Medical Journal Debate On Vitamin D Supplements Duringmentioning
confidence: 85%
See 2 more Smart Citations
“…However, the Norwegians in the cited study had far higher vitamin D levels than the UK Biobank participants at their initial evaluation, a subset increased their 25(OH)D levels significantly (p < 0.001) by initiating supplements, and, as in the study by Meng et al, vitamin D levels did increase significantly for the group as a whole over time (p < 0.01) (81). The authors of the most recent article using the UK BioBank study data did not address the issue of the use of potentially no longer accurate 25(OH)D levels in their preprint, but added a reference to the same Norwegian study as Darling et al, in their published article (77).…”
Section: Irish Medical Journal Debate On Vitamin D Supplements Duringmentioning
confidence: 85%
“…The Irish Medical Journal hosted a six-article formal debate on the topic in response to three published reports, including one by the researchers managing Ireland's part of the 26-country longitudinal study on aging (TILDA), in their May 2020 issue (72)(73)(74)(75). All three reports strongly recommended vitamin D supplements to help protect all adults in Ireland from COVID-19 while they are "cocooning" (not going outdoors) (72,73) Three research teams relied on the 2006-2010 UK Biobank data for the vitamin D levels included in their analyses of the relationship between COVID-19 incidence and vitamin D status (13,76,77). Roy et al, challenged the assertion that vitamin D levels are stable over time (important since levels were assessed 10-14 years prior to the pandemic) noting that the cited study only included women and followed up for only 5 years (13,78,79).…”
Section: Irish Medical Journal Debate On Vitamin D Supplements Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…Such that the compounding of risk factors in most deprived communities may result in the negative aftermath of the pandemic also being borne by those with the least resources to manage [20]. But this does not explain all the vulnerability [31], and it is worrying to note that an early review of deaths in health-care workers in the UK found 94% of the deaths in doctors were male and that 94% of the deaths in medical staff were nonwhite ethnicity [32].…”
Section: Men's Risk Of Sars-cov2mentioning
confidence: 99%
“…Ähnliche Ergebnisse liegen für das Infektionsrisiko mit akuten Atemwegserkrankungen auch aus anderen westlichen Ländern vor [21,22]. Gedrängte Wohnverhältnisse könnten also möglicherweise auch ein Risikofaktor für eine SARS-CoV-2-Infektion sein, wie erste Berichte aus den USA und Großbritannien vermuten lassen [23,24]. Wohnraum ist in vielen Ländern besonders in urbanen Regionen sozial ungleich verteilt, wie z.…”
Section: Soziale Ungleichheit Und Covid-19-risikofaktorenunclassified